METHOD OF ENCODING LOW-INFORMATIVE SEGMENTS OF THE VIDEO INFORMATION RESOURCE TO INCREASE THEIR AVAILABILITY - Buchyk, Serhii; Babenko , Yurii; Tsimura, Yurii; Pchelnikov, Sergii; Ushan, Vladyslav (Science-based technologies, 2023)
The significance of the video information resource for many applied areas is substantiated. This includes control systems, video control, monitoring, video conferencing. The presence of an imbalance between the levels of video stream intensity and the existing characteristics for ensuring the bandwidth of information and telecommunication systems is shown. This leads to a contradiction between the specified requirements for the quality characteristics of video services. Hence, there is a need to increase the level of availability of video information resources in the context of ensuring their integrity using information and telecommunication technologies. These technologies are used at different stages of video information delivery. One of the solutions to the formulated problem is the use of video stream coding technologies. However, the existing approaches do not sufficiently take into account the semantic and structural weight of the segments. This leads to loss of integrity in the face of increasing the level of video data compression. Hence, there is a contradiction for modern coding technologies. It is due to the presence of an inversely proportional relationship between the volume of encoded segments and the level of their semantic integrity. It is substantiated that low-informative segments allow the use of new processing processes. They provide a certain reduction in the bit volume of segments. It is shown that this creates the conditions for increasing the overall level of integrity of video resources. Therefore, the purpose of the article is to develop a method for encoding low-informative segments of a video information resource to increase their availability. A method for creating a syntactic description of the compact representation of segments is constructed. However, they do not affect the loss of semantic integrity of the video resource. The method includes the following processing steps. The first is to exclude the amount of psychovisual redundancy in time space based on: identification of areas of permissible correction according to a local indicator; round the base elements of the permissible correction area to six older bits. The second is to eliminate structural redundancy based on the formation of parameters to describe the area of permissible correction.